MENILAI KUALITAS LABA: FAKTOR PERTUMBUHAN LABA DAN UKURAN PERUSAHAAN PADA SEKTOR KESEHATAN - Aripratiwi, Ratna Anggraini; Anggreyani, Meilia Lestina Putri (Cahaya Ilmu Bangsa, 2024)
Maximizing profit is the goal of the company in increasing the company's growth, attracting investors and providing for future success. In this case, the factors that influence profit quality are profit growth and company size. This study aims to assess the effect of profit growth and company size on profit quality. The population used in the study were health sector companies listed on the IDX 2020-2023. Sampling in this quantitative study used purposive sampling and produced a sample of 68 company data. The data processing analysis method in this study was assisted by the use of the SPSS (Statistical Product and Service Solution) version 30 application. The results of this study indicate that profit growth has an effect on profit quality. While other results show that the study of company size does not affect profit quality